Democracy and Social Transition in the Baltic Sea Region - Latvia 2001 - Loftsson, Elfar; Choe, Yonhyok (Södertörn University, 2011)
This is the second survey conducted at the Södertörn University College by the project 'Democracy and Social Transition in the Baltic Sea Region'. The first survey was carried out in Estonia, Latvia and Lithuania in 1999. In connection with the follow-up survey in 2001, a similar survey was also carried out in Poland. To address peoples' perception on social and political changes, a number of questions was asked concerning: Political efficacy and political participation, political trust, evaluation of the electoral process, conceptions and evaluation of environmental issues, civil rights and duties, and an evaluation on household economy and economic situation. To acquire comparability with other Citizen Survey Studies conducted at Uppsala University in Sweden and at six university institutes of European countries, the modules are similar to their questions in structure and wordings.

This is the second survey conducted at the Södertörn University College by the project 'Democracy and Social Transition in the Baltic Sea Region'. The first survey was carried out in Estonia, Latvia and Lithuania in 1999. In connection with the follow-up survey in 2001, a similar survey was also carried out in Poland. To address peoples' perception on social and political changes, a number of questions was asked concerning: Political efficacy and political participation, political trust, evaluation of the electoral process, conceptions and evaluation of environmental issues, civil rights and duties, and an evaluation on household economy and economic situation. To acquire comparability with other Citizen Survey Studies conducted at Uppsala University in Sweden and at six university institutes of European countries, the modules are similar to their questions in structure and wordings.
Democracy and Social Transition in the Baltic Sea Region - Latvia 2001
Keywords: ELECTIONS; VAL; LEISURE TIME; FRITID; TRUST; FÖRTROENDE; CIVIL AND POLITICAL RIGHTS; MEDBORGERLIGA OCH POLITISKA RÄTTIGHETER; POLITICAL INTEREST; POLITISKT INTRESSE; POLITICAL BEHAVIOUR; POLITISKT BETEENDE; MEMBERSHIP; MEDLEMSKAP; POLITICAL INFLUENCE; MEDBORGARINFLYTANDE; POLITICAL PARTICIPATION; POLITISKT DELTAGANDE; AUTONOMY AT WORK; AUTONOMI I ARBETET; POLITICAL INSTITUTIONS; POLITISKA INSTITUTIONER; INTERNAL POLITICS; INRIKESPOLITIK; ELECTION CAMPAIGNS; VALKAMPANJER; WORKING CONDITIONS; ARBETSFÖRHÅLLANDEN; ORGANIZATIONS; ORGANISATIONER; SOCIAL PROTEST; SOCIAL PROTEST; Working conditions; Arbetsförhållanden; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Social behaviour and attitudes; Socialt beteende och attityder; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap